2021
DOI: 10.1007/s00221-021-06071-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of peripheral stimuli in shooters and handball players: an event-related potential study

Abstract: This study examined the practice-related sensitivity of automatic change detection. The visual mismatch negativity (vMMN) component of event-related potentials was compared in handball players and in sport shooters. Whereas effective performance in handball requires processing of a wide visual field, effective performance in shooting requires concentration to a narrow field. Thus, we hypothesized larger sensitivity to peripheral stimuli violating the regularity of sequential stimulation in handball players. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Regular physical activity had no effect on vMMN amplitude (Pesonen et al, 2019 ), but it reduced vMMN latency. Athletes from sports that demand the processing of a wider visual field were more sensitive to changes in the periphery than athletes from sports with strong focal attention demand (Petro et al, 2021 ). It is unknown whether this is an effect of practice or a part of trait differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular physical activity had no effect on vMMN amplitude (Pesonen et al, 2019 ), but it reduced vMMN latency. Athletes from sports that demand the processing of a wider visual field were more sensitive to changes in the periphery than athletes from sports with strong focal attention demand (Petro et al, 2021 ). It is unknown whether this is an effect of practice or a part of trait differences.…”
Section: Discussionmentioning
confidence: 99%
“…As we argued earlier (Czigler, 2007 ), in such an arrangement, participants can discover that, during the presentation of vMMN-related stimuli, there are no task-related changes; therefore, from time to time, they can observe the task-irrelevant events. Only a few studies applied continuous tasks such as tracking (Blacker et al, 2021 ; Petro et al, 2021 ) or a 2-back task (Sultson et al, 2019 ). What is really needed is research comparing vMMN to identical deviants in sequences with various task-related events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that N1 is acknowledged to be influenced by focused attention (Gonzalez et al, 1994;Luck & Hillyard, 1995;Mangun & Hillyard, 1991), it is plausible that the difference of N1 between rare and equiprobable conditions is modulated by focused attention. In previous studies, VMMN was modulated by spatial attention (File & Czigler, 2019;Petro et al, 2021;Suzuki, 2022). Therefore, it was predicted that P1 and N1 would be enhanced for central-deviant stimuli than for surrounding-deviant stimuli, N1 would differ between rare and equiprobable conditions for central-deviant stimuli but not for surrounding-deviant stimuli, and VMMN would be enhanced for central-deviant stimuli than for surrounding-deviant stimuli.…”
Section: Introductionmentioning
confidence: 96%
“…The VMMN is assumed to reflect a memory mismatch between current and predicted events (Kimura et al, 2011;Stefanics et al, 2014). Although the MMN is elicited in the absence of attention (Näätänen et al, 1978(Näätänen et al, , 2007, VMMN is modulated by spatial attention (File & Czigler, 2019;Petro et al, 2021;Suzuki, 2022). File and Czigler (2019) reported that VMMN was enhanced by deviant stimuli presented in an area closer to the attended visual field compared with outlying areas.…”
Section: Introductionmentioning
confidence: 99%